Mechanical loading and the synthesis of 1, 25(OH)2D in primary human osteoblasts. Issue 156 (February 2016) - van der Meijden, K.; Bakker, A.D.; van Essen, H.W.; Heijboer, A.C.; Schulten, E.A.J.M.; Lips, P.; Bravenboer, N.
Highlights: 1, 25(OH)2 D3 reduces the mechanical loading-induced NO response in primary human osteoblasts Mechanical loading increases mRNA levels of CYP27B1 in primary human osteoblasts The conversion rate of 25(OH)D3 to 1, 25(OH)2 D3 is not affected by mechanical loading in our model Mechanical loading reduces mRNA levels of VDR in primary human osteoblasts Abstract: The metabolite 1, 25-dihydroxyvitamin D (1, 25(OH)2 D) is synthesized from its precursor 25-hydroxyvitamin D (25(OH)D) by human osteoblasts leading to stimulation of osteoblast differentiation in an autocrine or paracrine way. Osteoblast differentiation is also stimulated by mechanical loading through activation of various responses in bone cells such as nitric oxide signaling. Whether mechanical loading affects osteoblast differentiation through an enhanced synthesis of 1, 25(OH)2 D by human osteoblasts is still unknown. We hypothesized that mechanical loading stimulates the synthesis of 1, 25(OH)2 D from 25(OH)D in primary human osteoblasts. Since the responsiveness of bone to mechanical stimuli can be altered by various endocrine factors, we also investigated whether 1, 25(OH)2 D or 25(OH)D affect the response of primary human osteoblasts to mechanical loading. Primary human osteoblasts were pre-incubated in medium with/without 25(OH)D3 (400 nM) or 1, 25(OH)2 D3 (100 nM) for 24 h and subjected to mechanical loading by pulsatile fluid flow (PFF). The response of osteoblasts to PFF was quantified by measuring nitric oxide, and by PCR analysis. The effect of PFF on the synthesis of 1, 25(OH)2 D3 was determined by subjecting osteoblasts to PFF followed by 24 h post-incubation in medium with/without 25(OH)D3 (400 nM). We showed that 1, 25(OH)2 D3 reduced the PFF-induced NO response in primary human osteoblasts. 25(OH)D3 did not significantly alter the NO response of primary human osteoblasts to PFF, but 25(OH)D3 increased osteocalcin and RANKL mRNA levels, similar to 1, 25(OH)2 D3 . PFF did not increase 1, 25(OH)2 D3 amounts in our model, even though PFF did increase CYP27B1 mRNA levels and reduced VDR mRNA levels. CYP24 mRNA levels were not affected by PFF, but were strongly increased by both 25(OH)D3 and 1, 25(OH)2 D3 . In conclusion, 1, 25(OH)2 D3 may affect the response of primary human osteoblasts to mechanical stimuli, at least with respect to NO production. Mechanical stimuli may affect local vitamin D metabolism in primary human osteoblasts. Our results suggest that 1, 25(OH)2 D3 and mechanical loading, both stimuli of the differentiation of osteoblasts, interact at the cellular level.